"A comparative study of the meaning of" Eli "in the verse of ablution from the perspective of Farraghan" - azadeh ebrahimy fakhary; vali allah jaafary; leila shams (پژوهش نامه معارف قرآنی, 2019)
The difference between the interpretative foundations in the verses of al-Ahkam has been the source of jurisprudential disputes. The literary foundations are around that letter. However, there is a need for further research in order to gain a clearer understanding of God and proper jurisprudential inference. This article deals with the comparative study of the meaning of "Eli" in the verse 6 of Surah Mubarak by analytical-critical method. Among the true and virtual meanings given to the word "Eli", the true meaning of "Eli" is "the end". The rest of the meanings like "Eli" meaning "Mo", "Explanation", "Fi", "Lam", "I", "Anand", "Ba" and the meaning of Emphasis are all virtual in their true meaning. Have been used. Farragin's commentators have considered the use of "Eli" in this verse to mean "Ma", "I", "Hadd" and "the end of the end". Literally the end of the sentence has been used and it is tempting to use the word iodine to determine the extent of hand washing. "Eli al-Mrafaq" is the subject of "Idicom". Given the necessity, lack of eloquence, lack of verse in terms of expressing the quality of the bath, abundant news and narrations, it is "Eli" to express the end of the brain rather than the bath, which is due to the iodine given to wash hands in ablution. And for reasons such as tradition, reason, consensus and custom, the quality of handwashing in the ablution of the elbows to the fingers is proven.